2018
DOI: 10.1017/wet.2018.48
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control with Halauxifen-Methyl Applied Alone and in Mixtures with 2,4-D, Dicamba, and Glyphosate

Abstract: Synthetic auxin herbicides such as 2,4-D and dicamba are often utilized to control broadleaf weeds in preplant burndown applications to soybean. Halauxifen-methyl is a new synthetic auxin herbicide for broadleaf weed control in preplant burndown applications to corn, cotton, and soybean at low use rates (5 g ae ha–1). Field experiments were conducted to evaluate efficacy and weed control spectrum of halauxifen-methyl applied alone and in mixtures with 2,4-D (560 g ae ha–1), dicamba (280 g ae ha–1), and glyphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 20 publications
7
35
1
2
Order By: Relevance
“…Furthermore, Kumar et al (2017) observed that fluroxypyr provided 83% to 88% control of GR horseweed 31 d after treatment (DAT), similar to the 89% control in this study. Previous research conducted by Zimmer et al (2018aZimmer et al ( , 2018b also found that halauxifen-methyl (5 g ai ha -1 ) provided 90% control of GR horseweed in soybean 35 DAT, comparable to the control observed in this study. In contrast, McCauley et al (2018) reported that halauxifen-methyl (5 g ha -1 ) provided 65% to 80% control of GR horseweed 28 DAT; their study was in a no-crop system, and plants ranged from 5 to 30 cm at application, whereas in this study all weeds were <10 cm tall, with crop competition, which may explain the lower control in that study.…”
Section: Gr Horseweedsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, Kumar et al (2017) observed that fluroxypyr provided 83% to 88% control of GR horseweed 31 d after treatment (DAT), similar to the 89% control in this study. Previous research conducted by Zimmer et al (2018aZimmer et al ( , 2018b also found that halauxifen-methyl (5 g ai ha -1 ) provided 90% control of GR horseweed in soybean 35 DAT, comparable to the control observed in this study. In contrast, McCauley et al (2018) reported that halauxifen-methyl (5 g ha -1 ) provided 65% to 80% control of GR horseweed 28 DAT; their study was in a no-crop system, and plants ranged from 5 to 30 cm at application, whereas in this study all weeds were <10 cm tall, with crop competition, which may explain the lower control in that study.…”
Section: Gr Horseweedsupporting
confidence: 88%
“…Similar to this study, Mahoney et al (2016) reported that 2,4-D, clopyralid, fluroxypyr þ MCPA, and pyrasulfotole/bromoxynil reduced GR horseweed density by 94% to 99%. In contrast, Zimmer et al (2018a) reported that halauxifen-methyl applied in soybean reduced GR horseweed density by 76%.…”
Section: Density and Biomassmentioning
confidence: 89%
“…These data from North Carolina and Virginia, in addition to research from Indiana (Zimmer et al 2018a(Zimmer et al , 2018b, indicate halauxifen-methyl effectively controls horseweed. In this experiment, halauxifen-methyl and dicamba controlled horseweed averaging 5 or 15 cm in height more effectively than did 2,4-D.…”
Section: Resultsmentioning
confidence: 62%
“…Other members of the pyridine-2-carboxylate family include picloram, clopyralid, and aminopyralid (Epp et al 2016). Halauxifen-methyl effectively controls horseweed at varying sizes (McCauley and Young 2016;Zimmer et al 2018a, Zimmer et. al 2018b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation